Green synthesis and characterization of AgNp silver nanoparticles stabilized in jurema preta extract (Mimosa tenuiflora) (Research, Society and Development, 2022)
The research aimed to synthesize and characterize AgNps from silver nitrate (AgNO3) in Mimosa tenuiflora extract. The methodology adopted was laboratory of a quantitative nature. For the production of the extract, the powder of mimosa husks plus distilled water was used. In the synthesis of the nanoparticles, 100 mL of 1.0mmol/L (AgNO3) was used, heated in magnetic stirring and 1.0 mL of 1% sodium citrate was dripped onto the nitrate solution. Upon reaching room temperature, the mimosa extract was added to the mixture. The nanoparticles were characterized (UV-Vis), in a scanning range 1900-900nm, slit aperture=2.0 nm and spectral solution of 1.0 nm. As for the results, the isolated analyzes of the solutions did not show an absorbance peak on a visible wavelength scale between 400 and 600 nm. In the analysis of the mixtures of AgNO3/Na3C6H5O7 and AgNO3/NaBH4, it showed the formation of maximum absorbance peaks of 420nm for the silver nitrate solution in citrate contact and 390nm for the silver nitrate solution in contact with the borohydride. The analysis of the AgNO3/mimosa/Na3C6H5O7 and AgNO3/mimosa/NaBH3 solution showed a maximum absorbance peak of 450nm for the silver nitrate/mimosa/citrate solution and of 400nm for the silver nitrate/mimosa/borohydride solution on a scale wavelength between 300 to 600nm. According to the results found, it can be seen that the mimosa extract presents ideal conditions for the synthesis and stabilization of nanoparticles.